New development: Using the Vanguard Method to explore demand and performance in people-centred services. Issue 5 (4th July 2021) - Hood, Rick; O'Donovan, Brendan; Gibson, Jo; Brady, Dermot
ABSTRACT: Demand is rising for people-centred services in areas such as health, social care and housing. Such services generally seek to manage demand through layers of triage and assessment, reserving their specialist functions for people assessed with complex or acute needs. This article draws on the experience of managers from a range of public and voluntary sector organizations, who, as part of a postgraduate university course, used the Vanguard Method to explore demand and performance in their services. Their work suggests that excessive focus on gatekeeping and functional specialization is preventing services from understanding their users, which unwittingly helps to drive up demand. The authors discuss the prospect of designing services that reduce demand by becoming more people-shaped.